2009
DOI: 10.1029/2008jb006077
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of the asthenosphere from glacial isostatic adjustment and subduction dynamics at the northern Cascadia subduction zone, British Columbia, Canada

Abstract: [1] Late glacial sea level curves located in the Cascadia subduction zone (CSZ) fore arc in southwestern British Columbia show that glacial isostatic adjustment (GIA) was rapid when the Cordilleran Ice Sheet collapsed in the late Pleistocene. GIA modeling with a linear Maxwell rheology indicates that the observations can be equally well fit across a wide range of asthenospheric thicknesses, provided that the asthenospheric viscosity is varied from 3 Â 10 18 Pa s for a thin (140 km) asthenosphere to 4 Â 10 19 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 75 publications
(98 reference statements)
12
79
2
Order By: Relevance
“…This regular and relatively recent decline is different from that interpreted for northern Cascadia, where rebound was thought to be complete by the early Holocene (e.g. Mathews et al, 1970;James et al, 2009b). At Coos Bay, Oregon, however, Nelson et al (1996a) argued for a more punctuated RSL rise in the mid-to late-Holocene.…”
Section: Southern Cascadiacontrasting
confidence: 60%
“…This regular and relatively recent decline is different from that interpreted for northern Cascadia, where rebound was thought to be complete by the early Holocene (e.g. Mathews et al, 1970;James et al, 2009b). At Coos Bay, Oregon, however, Nelson et al (1996a) argued for a more punctuated RSL rise in the mid-to late-Holocene.…”
Section: Southern Cascadiacontrasting
confidence: 60%
“…CC BY 4.0 License. flow may sufficiently describe both processes due to the similarity of the timescales over which they take place (James et al, 2009). There is the additional complication that afterslip must be accounted for in post-seismic studies (Ingleby and Wright, 2017), but in general, the changing deformation rates observed during an earthquake cycle suggest that the Earth either follows a power-law rheology (Freed and Burgmann, 2004;Freed et al, 2006), or a rheology comprising several different 820 relaxation times (Pollitz, 2005;Hetland and Hager, 2006).…”
Section: Low Viscosity Regionsmentioning
confidence: 99%
“…Deglacial RSL histories of the Pacific coast [75][76][77][78][79][80][81][82][83][84][85] are supplemented by studies of the earthquake and tsunami history of the Cascadia subduction zone along the coasts of British Columbia, Washington, Oregon, and northern California [86][87][88][89][90][91][92][93].…”
Section: Pacific Coastmentioning
confidence: 99%
“…Regions formerly covered by the Cordilleran ice sheet (southern Alaska to Puget Sound, Washington) are strongly influenced by local ice loading, which results in variable RSL histories [85]. In northwest Georgia Strait, RSL fell from a marine limit as much as 154 m at 14 ka to a lowstand of >−25 m at 11 ka after deglaciation due to glacio-isostatic uplift.…”
Section: Pacific Coastmentioning
confidence: 99%